2009
DOI: 10.1371/journal.pone.0004179
|View full text |Cite
|
Sign up to set email alerts
|

Ets1 Induces Dysplastic Changes When Expressed in Terminally-Differentiating Squamous Epidermal Cells

Abstract: BackgroundEts1 is an oncogene that functions as a transcription factor and regulates the activity of many genes potentially important for tumor initiation and progression. Interestingly, the Ets1 oncogene is over-expressed in many human squamous cell cancers and over-expression is highly correlated with invasion and metastasis. Thus, Ets1 is believed to mainly play a role in later stages of the oncogenic process, but not early events.Methodology/Principal FindingsTo better define the role of Ets1 in squamous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 68 publications
3
40
0
Order By: Relevance
“…In normal tissues, Ets1 is expressed only in the basal layer of stratified squamous epithelium (Nagarajan et al, 2009). However, in a large fraction of SCC tumors, Ets1 is highly expressed within the malignant keratinocytes, and its levels directly correlate with the invasive and metastatic potential of the tumor (Bai et al, 2009;Endo et al, 2006;Keehn et al, 2004;Pande et al, 1999;Saeki et al, 2000;Vairaktaris et al, 2007).…”
Section: Ets1 Blocks Terminal Differentiation Of Keratinocytes and Inmentioning
confidence: 99%
See 4 more Smart Citations
“…In normal tissues, Ets1 is expressed only in the basal layer of stratified squamous epithelium (Nagarajan et al, 2009). However, in a large fraction of SCC tumors, Ets1 is highly expressed within the malignant keratinocytes, and its levels directly correlate with the invasive and metastatic potential of the tumor (Bai et al, 2009;Endo et al, 2006;Keehn et al, 2004;Pande et al, 1999;Saeki et al, 2000;Vairaktaris et al, 2007).…”
Section: Ets1 Blocks Terminal Differentiation Of Keratinocytes and Inmentioning
confidence: 99%
“…However, in a large fraction of SCC tumors, Ets1 is highly expressed within the malignant keratinocytes, and its levels directly correlate with the invasive and metastatic potential of the tumor (Bai et al, 2009;Endo et al, 2006;Keehn et al, 2004;Pande et al, 1999;Saeki et al, 2000;Vairaktaris et al, 2007). Tumors that express high levels of Ets1 typically also express high levels of several matrix metalloprotease (Mmp) genes (Dittmer, 2003;Hahne et al, 2008;Lincoln and Bove, 2005) and Ets1 has been shown to directly regulate expression of multiple Mmp genes (Baillat et al, 2006;Nagarajan et al, 2009;Ozaki et al, 2000;Reisdorff et al, 2002;Wei et al, 2009;Westermarck et al, 1997). Yet, it has been unclear whether the sole oncogenic role of Ets1 is upregulation of Mmp expression or whether this protein also promotes squamous cell carcinoma development by affecting other pathways.…”
Section: Ets1 Blocks Terminal Differentiation Of Keratinocytes and Inmentioning
confidence: 99%
See 3 more Smart Citations